Celiac artery compression syndrome: Report of a case and literature review - Gürol ÖKSÜZOĞLU; Yücel ÜSTÜNDAĞ; Mehmet İNAN and Arif ÖZDEMİR and Ahmet ÖZENÇ and Burhan KAYHAN (Turkish Journal of Gastroenterology, 2019)
-